If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 4n + -1 Reorder the terms: 7 = -1 + 4n Solving 7 = -1 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 7 + -4n = -1 + 4n + -4n Combine like terms: 4n + -4n = 0 7 + -4n = -1 + 0 7 + -4n = -1 Add '-7' to each side of the equation. 7 + -7 + -4n = -1 + -7 Combine like terms: 7 + -7 = 0 0 + -4n = -1 + -7 -4n = -1 + -7 Combine like terms: -1 + -7 = -8 -4n = -8 Divide each side by '-4'. n = 2 Simplifying n = 2
| 5n+12=75-4n | | 12k+5=k+45 | | 40+14y=2(-4y-13) | | 4x+90=7x+42 | | 2x+5y+3+7x+2y+7= | | n+(n-1)=5 | | 2x+24=3x-17 | | -8p+6p=6 | | 6n-7=5 | | 6r-7=7r-10 | | 6x+21=3x+66 | | 25x^2-27x=0 | | x+y=e | | 6n+7n=13 | | 6x+26=4x+66 | | (x+7)6=15x | | -8=4n-4 | | X+2(0)=-6 | | 7x+20=2x+115 | | (x+7)6=15 | | 5f=41-3f-9 | | 0+2y=-6 | | -a+y=2a-8 | | 4-4n=-8 | | 4-4n=18 | | 2x+132=8x+66 | | x(2x-1)-10=-2x(1-x) | | 8d-18-d=d | | 43y-35=0 | | 13x-2x=44 | | -34+24=-5x+7x | | -11m=-132 |